Rethinking rescue : Dog Lady and the story of America's forgotten people and pets - Mithers, Carol Lynn (Counterpoint, 2024)
"In Los Angeles's most underserved communities, Lori Weise is known as the Dog Lady, the woman who's spent decades caring for people in poverty and the animals that love them. Long before anyone else, Weise grasped that animal and human suffering are inextricably connected and created a new rescue narrative, an enduring safety net empowering pet owners and providing resources to reduce the number of pets coming into shelters. Rethinking Rescue unites the causes of animal welfare and social justice, moving between Weise's story and that of the U.S. rescue movement: from the dog's twentieth-century transition from property to family to the rise of the no kill campaign to stop shelter euthanasia and the contradictions that hampered those efforts. Through captivating storytelling and investigative reporting, Carol Mithers examines the consequences of bias within this overwhelmingly white movement, where an overemphasis on placing animals in affluent homes often disregards pet owners in poverty. Weise's innovative and ultimately triumphant efforts revealed a better way"--